(untitled) (American Journal of Arts and Human Science, 2024)
The study examines the correlation between 21st-century teaching skills and teachers’ performance using the Classroom Observation Tool (COT) among public Junior High School teachers in Region X during the 2023-2024 school year. It aims to assess teachers’ profiles, 21st-century skills, performance levels, and the relationship between these factors. Statistical analysis revealed that collaboration and 21st-century skills had the most significant impact, while digital literacy scored the lowest. Educational attainment moderately influenced teachers’ assessment of 21st-century skills. Position, teaching experience, and educational attainment moderately affected performance. An instructional development plan was formulated to enhance teaching skills, emphasizing the importance of professional development in digital technology. Teachers are encouraged to improve digital integration skills through training on emerging technologies and methodologies for effective technology integration in teaching practices. This plan aims to enhance teaching quality and performance by ensuring a consistent and advanced use of digital tools in education.